PERLINDUNGAN HUKUM PENCIPTA KARYA PAHAT DALAM PEMANFAATAN AUGMENTED REALITY DI MUSEUM KEBANGKITAN NASIONAL: Legal Protection for Sculptors in the Use of Augmented Reality at the Museum Kebangkitan Nasional - Akmal Abdussalam Mahmud; Simona Bustani (Faculty of Law, Universitas Trisakti, 2025)
This research focuses on the legal protection of creators of sculptural works that use Augmented Reality (AR) technology as a means of publication at the National Awakening Museum in Jakarta. AR technology that integrates virtual elements into the real world provides an interactive experience for museum visitors, but at the same time presents new challenges in copyright protection. The problem identification in this research concerns how legal protection based on Law No. 28 of 2014 concerning Copyright against digital art creations should be published through AR. This article is a normative legal research and is descriptive, using secondary data and interviews with the National Awakening Museum Jakarta. The results and conclusions show that sculptural works published using AR technology require comprehensive legal protection, including the creator's moral and economic rights. However, there are gaps in the implementation of such protection, especially in the face of potential copyright infringement in the digital era. This research suggests more specific regulations and increased public awareness of the importance of copyright protection in the technological age.